2022
DOI: 10.1111/jfpp.17157
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of pomegranate peel extract as antifungal coating agent against Fusarium oxysporum on tomatoes

Abstract: The shelf life of tomato is limited due to its perishable nature. The fruit is highly susceptible to fungal attack such as Fusarium oxysporum. The edible coating has been used to enhance the postharvest life of different food products. The present study was designed for the development of edible antifungal coating on tomato fruit using pomegranate peel extract in combination with chitosan. Pomegranate peel extract was obtained from pomegranate peel using water distillation method. The antifungal coating was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Pomegranate and pomegranate extract can be in the form of liquid or powder; these natural ingredients extend the shelf life of food and beverage products without adverse effects on taste and visuals while, at the same time, allowing for convenience and safety [21,22]. Saeed et al [18] reported that pomegranate peel extract was an effective antimicrobial coating material for tomatoes. They found that the coated tomatoes were firmer and had more lycopene content than the control, and the coating materials did not affect the sensory profile of tomatoes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pomegranate and pomegranate extract can be in the form of liquid or powder; these natural ingredients extend the shelf life of food and beverage products without adverse effects on taste and visuals while, at the same time, allowing for convenience and safety [21,22]. Saeed et al [18] reported that pomegranate peel extract was an effective antimicrobial coating material for tomatoes. They found that the coated tomatoes were firmer and had more lycopene content than the control, and the coating materials did not affect the sensory profile of tomatoes.…”
Section: Discussionmentioning
confidence: 99%
“…Food product manufacturers are interested in utilizing natural plant-derived preservatives to inhibit bacteria such as Listeria spp. and E. coli as a means to reduce the use of synthetic additives and ensure food safety with extended shelf life [4,18]. Therefore, the objectives of this study were to investigate the antimicrobial effects of pomegranate juice at different concentrations against L. innocua and E. coli and determine the treatment effects in distilled water (DW) and bacterial culture broth systems at different temperatures.…”
Section: Introductionmentioning
confidence: 99%